Cic1, an adaptor protein specifically linking the 26S proteasome to its substrate, the SCF component Cdc4 - Jäger, Sibylle (Oxford University Press, 2001)
In eukaryotes, the ubiquitin–proteasome system plays a major role in selective protein breakdown for cellular regulation. Here we report the discovery of a new essential component of this degradation machinery. We found the Saccharomyces cerevisiae protein Cic1 attached to 26S proteasomes playing a crucial role in substrate specificity for proteasomal destruction. Whereas degradation of short-lived test proteins is not affected, cic1 mutants stabilize the F-box proteins Cdc4 and Grr1, substrate recognition subunits of the SCF complex. Cic1 interacts in vitro and in vivo with Cdc4, suggesting a function as a new kind of substrate recruiting factor or adaptor associated with the proteasome.